Resilience as a focus of suicide research and prevention. (20th June 2019) - Sher, L.
Abstract : Suicide is a major medical and social problem. Decades of suicide research have mostly focused on risk factors for suicidal behaviour while overlooking protective factors such as resilience that may help to address this important public health issue. Resilience is the capacity and dynamic process of adaptively overcoming stress and adversity while maintaining normal psychological and physical functioning. Studies conducted over the past 10–15 years suggest that resilience is a protective factor against suicide risk. Resilience is becoming a focus of suicide research and prevention. Building resilience should be a part of universal, selective, and indicated suicide prevention interventions. Promoting resilience may reduce suicide risk in the general population, in groups at elevated suicide risk, and among high‐risk individuals. Building resilience in the general population may reduce the incidence of stress‐related disorders and, consequently, suicidal behaviour. Improving resilience should be a part of a treatment plan of every psychiatric patient. Mental health professionals will probably have the best success in reducing suicide risk in psychiatric patients if they actively concentrate on increasing stress resilience using both psychosocial and pharmacological interventions. It is critically important to move forward the development of pharmacological and psychological interventions for enhancing resilience.